Review of health information systems in India - Samhita, Kasani (Запорізький державний медичний університет, 2021)
Today when Internet and systems for receiving, accumulating, transmitting, processing and analyzing information cover all countries, it is obvious that medical information systems are of significant interest. This is especially important in countries like India, with a population of 1.21 billion residing in over 3.2 million square km area hindered by varied landscapes.
Keywords: тези